Cervical Disk Arthroplasty and Range of Motion at 7 Years: Impact on Adjacent Level Degeneration. Issue 3 (20th April 2023) - Satin, Alexander M.; Rogers-LaVanne, Mary P.; Derman, Peter B.
Abstract : Study Design: Secondary analysis of data collected in a prospective, randomized, noninferiority Food and Drug Administration (FDA) Investigational Device Exemption (IDE) clinical trial. Objective: The objective of this study was to evaluate the impact of range of motion (ROM) following single-level cervical disk arthroplasty (CDA) on the development of radiographic adjacent level degeneration (ALD). Summary of Background Data: The rationale for CDA is that maintenance of index-level ROM will decrease adjacent level stresses and ultimately reduce the development of ALD compared with anterior cervical discectomy and fusion. However, little information is available on the impact of hypermobility on the development of ALD after CDA. Materials and Methods: Radiographic assessments were evaluated for index-level flexion-extension ROM and ALD. Continuous data was assessed using 1-way analysis of variance. The relationship between ALD progression and ROM was evaluated using χ 2 tests. The α was set at 0.05. Results: More ALD progression was observed after anterior cervical discectomy and fusion than CDA ( P =0.002 at the superior and P =0.049 at the inferior level). Furthermore, there was an association between ALD progression and ROM ( P =0.014 at the superior level and P =0.050 at the inferior level) where patients with mid-ROM after CDA experienced the lowest frequency of ALD progression at the superior and inferior levels. Patients with the lowest and highest ROM after CDA experienced a greater increase in ALD score at the inferior level ( P =0.046). Sex and age were associated with ROM groups ( P =0.001 and 0.023, respectively). Conclusions: While maintenance of index-level ROM is protective after CDA, patients with the highest ROM after CDA have similar rates of ALD progression to the lowest ROM and greater increases in ALD compared with mid-ROM after CDA. High ROM after CDA may contribute to ALD progression.